Interspecies Interactions within Oral Microbial Communities - Kuramitsu, Howard K. (American Society for Microbiology (ASM), 2007)
Summary: While reductionism has greatly advanced microbiology in the past 400 years, assembly of smaller pieces just could not explain the whole! Modern microbiologists are learning “system thinking” and “holism.” Such an approach is changing our understanding of microbial physiology and our ability to diagnose/treat microbial infections. This review uses oral microbial communities as a focal point to describe this new trend. With the common name “dental plaque,” oral microbial communities are some of the most complex microbial floras in the human body, consisting of more than 700 different bacterial species. For a very long time, oral microbiologists endeavored to use reductionism to identify the key genes or key pathogens responsible for oral microbial pathogenesis. The limitations of reductionism forced scientists to begin adopting new strategies using emerging concepts such as interspecies interaction, microbial community, biofilms, polymicrobial disease, etc. These new research directions indicate that the whole is much more than the simple sum of its parts, since the interactions between different parts resulted in many new physiological functions which cannot be observed with individual components. This review describes some of these interesting interspecies-interaction scenarios.